Mine Backfilling in the Permafrost, Part I: Numerical Prediction of Thermal Curing Conditions within the Cemented Paste Backfill Matrix - Fabrice Beya; Mamert Mbonimpa; Tikou Belem; Li Li; Ugo Marceau; Patrick Kalonji; Mostafa Benzaazoua; Serge Ouellet (Minerals, 2019)
The mechanical behavior of cemented paste backfill (CPB) in permafrost regions may depend on the thermal curing conditions. However, few experimental data are available for calibrating and validating numerical models used to predict these conditions. To fill this gap, a three-dimensional (3D) laboratory heat transfer test was conducted on CPB placed in an instrumented barrel and cured under a constant temperature of −11 °C. Results were used to calibrate and validate a numerical model built with COMSOL Multiphysics®. The model was then used to predict the evolution of the temperature field for CPB cured under the thermal boundary conditions for a backfilled mine stope in the permafrost (at −6 °C). Numerical results indicated that the CPB temperature gradually decreased with time such that the entire CPB mass was frozen about five years after stope backfilling. However, the permafrost equilibrium temperature of −6 °C was not reached throughout the entire CPB mass even after 20 years of curing. In addition, the evolution of the temperature field in the permafrost rock showed that the thickness of the thawed portion reached about 1 m within 120 days. Afterwards, the temperature continues to drop over time and the thawed portion of the permafrost refreezes after 365 days.